The Effect of Youth's Healthy Packages on Premenstrual Syndrome - Mulyati, Sri; Widiawati, Ida (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Abstract— Most women of reproductive age have premenstrual symptoms which consist of emotional and physical symptoms. Many factors can affect PMS including physical activity, nutrition such as drinks containing calcium and ginger, massage and other factors. This study aims to determine the effect of a healthy package consisting of (exercise, giving ginger milk and effleurage massage) on premenstrual syndrome. The design of this study was a quasi-experimental pre-post with control group. The research variables were measured in 2 groups, There are the intervention group and the control group. The number of samples in this study consisted of 38 girls in the intervention group and 38 girls in the control group with simple random sampling. The analysis used univariate (frequency distribution) and bivariate (T Test, Chi-Square). The results showed that there was an influence between the effect of a healthy adolescent package (consisting of exercise, giving ginger milk and eflleurage massage) on premenstrual syndrome. Keywords— Pre Menstrual Syndrome, Exercise, Ginger Milk, Eflleurage Massage